2022
DOI: 10.1111/mec.16483
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐level genome assembly for takin (Budorcas taxicolor) provides insights into its taxonomic status and genetic diversity

Abstract: The takin (Budorcas taxicolor) is a large bovid herbivore, belonging to the subfamily Caprinae. The number of takins was estimated to be only 7000-12,000 (Cheng et al., 2020) and it has been listed as vulnerable by the International Union for Conservation of Nature (IUCN) (Zeng & Song, 2002). It was divided into four subspecies according to physiological characteristics and geographical location (Wu, 1986). Qinling takin (Bu. t. bedfordi) and Sichuan takin (Bu. t. tibetana) are confined to China, while the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…The nucleotide diversity of B. t. bedfordi analysed by the mtDNA D-loop region was 0.0021 [ 48 ], indicating low genetic diversity [ 49 ]. The single nucleotide variants of B. t. bedfordi analysed by SNP were lower than those of the giant panda, golden monkey, goat, and cattle [ 50 52 ]. These results indicated that the B. t. bedfordi population suffered from poor genetic diversity, which was in accordance with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide diversity of B. t. bedfordi analysed by the mtDNA D-loop region was 0.0021 [ 48 ], indicating low genetic diversity [ 49 ]. The single nucleotide variants of B. t. bedfordi analysed by SNP were lower than those of the giant panda, golden monkey, goat, and cattle [ 50 52 ]. These results indicated that the B. t. bedfordi population suffered from poor genetic diversity, which was in accordance with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue includes examples of long‐read genome‐scale analyses in vulnerable or threatened species. For instance, Li, Yang, et al (2023) rely on PacBio data and Hi‐C technology to assemble the genome of the takin, a large bovid herbivore currently listed as vulnerable by the International Union for Conservation of Nature (IUCN; Li, Yang, et al, 2023). This high‐quality chromosome‐level assembly was used, along with resequencing data, to demonstrate important declines in effective population size during the past million years, and to uncover evidence of runs of homozygosity caused by recent inbreeding.…”
Section: Conservation Genomicsmentioning
confidence: 99%
“…The first reference genome assembly for the high-extinction-risk Qinling serow has been made possible in large part by the use of HiFi sequencing technology in the field of animal conservation. This historic achievement has since laid the groundwork for investigating the evolutionary history of the Qin-ling serow and clarifying the fundamental causes of its elevated extinction risk [121]. Technological innovation resulting from the genetic revolution has profound consequences for the conservation of plant resources and their inherent diversity, as well as for the protection of animal resources [122].…”
Section: Biodiversitymentioning
confidence: 99%